Niveles de Pseudocolinesterasa en relación al tiempo de exposición y normas de manipulación de plaguicidas en agricultores del Barrio La Era de la parroquia El Tambo del cantón Catamayo. - Cuenca, Cinthya (2013)
Pseudocholinesterase called the plasma cholinesterase, is generally present in a soluble form in almost every tissue in the liver and plasma, but in low concentration in the nervous system. This enzyme hydrolyzed: the butyrylcholine 4 times faster than acetylcholine, butyrylcholine preventing accumulation in the liver, hydrolyzing quickly. Clinically is considered indicative of a possible poisoning organophosphate and carbamate insecticides. Carbamate pesticides cause a reversible inhibition of this enzyme and that the binding is reversible enzimacarbamil, which causes a milder clinical syndrome with a shorter duration, in organophosphate poisoning this union is irreversible. The main purpose of this research was to: Determine Pseudocholinesterase levels in relation to time of exposure and pesticide handling rules in farmers Barrio La Era de la Parroquia El Tambo del Cantón Catamayo. The study was descriptive cross-sectional, the research universe was 214 farmers, of which taking inclusion criteria, the sample consisted of 57 patients, consisting of 38 persons were male and 19 female persons. They were given a survey based on the time of exposure and pesticide handling rules. Spectrophotometrically detected in the samples obtained after fumigation decreased values ​​(25 ° C - 30 ° C: ˂ 3000 U / L), in males 9 people (24%) and in females 2 people (11%), which is considered indicative of a possible mild intoxication. Keywords: Pseudocholinesterase, organophosphates, carbamates.